Strategi Nahdlatul Ulama dalam Mempertahankan Posisi dan Legitimasi di Arena Islam Indonesia - M Mujibuddin (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2019)
This article aims to analyze NU strategy in maintaining the arena of moderate Islam in Indonesia. this strategy was used by NU to anticipate the radical movement intending to seize the Indonesian Islamic arena. This is because NU has legitimacy as a moderate organization in Indonesia. This study uses observational studies by looking at the historicity of NU as a religious organization and its role in the Indonesian Islamic arena. This study uses the theory of genetic structuralism which includes habitus, arena, capital, trajectory, and strategy. The results of this study indicate that NU basically has the capital to maintain the arena of moderate Islam in Indonesia. The accumulation of capital is then at stake with two strategies, that efforts to maintain and widen the arena of power in Islam in Indonesia has a great opportunity.